A prototype of a portable optical sensor for the detection of transparent and translucent microplastics in freshwater. (September 2019) - Asamoah, Benjamin O.; Kanyathare, Boniphace; Roussey, Matthieu; Peiponen, Kai-Erik
Abstract: Microplastic pollution in water bodies is an alarming problem which needs to be addressed. However, issues such as size, shape and their appearance to light (transparent or translucent) make it difficult to be optically detected. Here, a feasibility study of a portable prototype optical sensor with the capability of measuring simultaneously specular laser light reflection and transmission from microplastic particles is presented. The specular reflection signal and the transmitted interference pattern were recorded with a photodiode and a CCD camera, respectively. With the combination of these two modes of detection, it is possible to screen the type, size, and nonplanarity of two microplastics types, i.e., transparent polyethylene terephthalate (PET) and translucent low-density polyethylene (LDPE), in a volume of freshwater, with high confidence. In principle, the prototype could be used for the detection of both floating microplastics as well as microplastics experiencing sedimentation in natural water bodies, and in water filtration in water treatment plants. Graphical abstract: Image 1034309 Highlights: Development of a prototype optical sensor for microplastics detection. Detection of transparent and translucent plastic particles in water bodies. Monitoring of light-microplastic interactions in water.